SYMPTOMS AND ENDOSCOPIC FEATURES AT BARRETT'S OESOPHAGUS DIAGNOSIS: IMPLICATIONS FOR NEOPLASTIC PROGRESSION RISK. (8th June 2013) - Coleman, H G; Bhat, S; Murray, L J; McManus, D; Gavin, A T; Johnston, B T
Abstract : Introduction: Risk stratification of Barrett's oesophagus (BO) patients based on clinical and endoscopic features may help to optimise surveillance for early detection/prevention of oesophageal adenocarcinoma (OAC) development. Aims/Background: The aim of this study was to investigate patient symptoms and endoscopic features at index endoscopy and risk of neoplastic progression in a large population-based cohort of BO patients. Method: A retrospective review of hospital records relating to incident BO diagnosis was conducted in a subset of patients with specialised intestinal metaplasia from the Northern Ireland BO register. Patients were matched to the Northern Ireland Cancer Registry to identify progressors to adenocarcinoma of the oesophagus or oesophageal high grade dysplasia (HGD). Cox proportional hazards models were applied to evaluate the association between symptoms, endoscopic features and neoplastic progression risk. Results: During 27, 997 person-years of follow-up, 128 of 3.148 BO patients progressed to develop HGD or adenocarcinoma of the oesophagus. Ulceration within the Barrett's segment, but not elsewhere in the oesophagus, was associated with an increased risk of progression (HR 1.72; 95%CI: 1.08–2.76). Long segment BO carried a significant 7-fold increased risk of progression compared with short segment BO. When considering only cancer outcomes, a reported weight loss of >5kg at incident BO was predictive of a doubled risk of progression to cancer, even up to 5 years post-BO diagnosis. Conversely, experiencing reflux symptoms was associated with a decreased risk of cancer progression (HR 0.62; 95%CI: 0.41-0.95). Conclusion: BO patients presenting with a Barrett's ulcer, substantial weight loss or long segment BO have an increased risk of progressing to HGD/OAC and should be considered for more frequent surveillance.